Successful Use of Higher-Dose Etanercept for Multirefractory Systemic Flare of Adult-Onset Still’s Disease with Liver Failure with No Response to Tocilizumab Therapy - Taio Naniwa; Shinya Tamechika; Shiho Iwagaitsu; Shinji Maeda; Hiroyuki Togawa (Case Reports in Rheumatology)
A 21-year-old woman with refractory systemic flare of adult-onset Still’s disease with liver failure despite high-dose corticosteroids, cyclosporine, tacrolimus, and tocilizumab, was successfully treated with additional use of etanercept. Etanercept at a dose of 50 mg weekly was partially effective but could not reduce the dose of concomitant betamethasone from 5 mg/day. Etanercept at a dose of 75 mg weekly could lead her to clinical remission and enabled successful tapering off the corticosteroids and discontinuation of etanercept. Normalization of serum C-reactive protein and interleukin 6 and persistent elevation of serum tumor necrosis factor α under the treatment with high-dose corticosteroids and immunosuppressants suggest that tumor necrosis factor α was more deeply involved than at least interleukin 6 in the pathogenesis of refractoriness of the disease in this patient, and these findings might be indicative of potential efficacy for adjunctive use of a tumor necrosis factor inhibitor rather than an interleukin 6 inhibitor.